A new reservoir model to support environmental monitoring of the Orakeikorako geothermal system. (January 2016) - O'Sullivan, John; Arthur, Simon; O'Sullivan, Mike
Highlights: A new reservoir model is developed to support monitoring of the Orakeikorako system. A very high resolution grid is used in the shallow zone to capture surface activity. A detailed geological structure, with several faults explicitly represented. The model was calibrated with extensive surface data but limited downhole data. The approach can be applied to other protected geothermal systems. Abstract: Orakeikorako is one of several protected geothermal systems in the Taupo Volcanic Zone (TVZ) in the centre of the north island of New Zealand. Its beautiful surface features are highly valued for both their cultural significance and for tourism. Many other geothermal systems in the TVZ have been developed for energy utilisation including Ngatamariki which borders Orakeikorako. The interaction of geothermal systems is poorly understood and is an area of active research in New Zealand. A new reservoir model has been developed to support environmental monitoring of the Orakeikorako system and to assist future investigations of its interaction with neighbouring geothermal systems. It also demonstrates that accurate reservoir models can be developed by using detailed surface measurements for calibration when down-hole data are not available. This is important both for modelling protected geothermal systems and also for assessment of systems in the early stages of development.